Acute Aortocaval Fistula Secondary to Chronic Type 1 B Abdominal Aortic Aneurysm Endoleak - Mouawad, Nicolas J.; Quarrie, Ricardo; Starr, Jean (International Journal of Angiology, 2020)
Aortocaval fistula (ACF) is a rare complication of abdominal aortic aneurysms (AAA), involving less than 1% of all AAA and is associated with high morbidity and mortality; it is even more uncommon, following endovascular aneurysm repair. The clinical presentation can be variable and making the diagnosis can be difficult. It can present with symptoms and signs of an abdominal emergency or systemic hypoperfusion. The traditional method of repair has been open surgery, which is associated with a high mortality rate. Endovascular repair has become more common, but results are difficult to interpret due to the low incidence of ACF. A high index of suspicion is imperative to avoid delay in diagnosis and care.
Keywords: aortocaval fistula; abdominal aortic aneurysm complication; endoleak